2019
DOI: 10.1038/s41388-019-1003-3
|View full text |Cite|
|
Sign up to set email alerts
|

The Epstein–Barr virus nuclear antigen-1 upregulates the cellular antioxidant defense to enable B-cell growth transformation and immortalization

Abstract: Epstein-Barr virus (EBV) immortalizes human B-lymphocytes and is implicated in the pathogenesis of lymphoid and epithelial cell malignancies. The EBV nuclear antigen (EBNA)-1 induces the accumulation of reactive oxygen species (ROS), which enables B-cell immortalization but causes oxidative DNA damage and triggers antiproliferative DNA damage responses. By comparing pairs of EBV-negative and-positive tumor cell lines we found that, while associated with the accumulation of oxidized nucleotides, EBV carriage pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
(62 reference statements)
0
14
0
1
Order By: Relevance
“…Latent viral proteins expression also modulate intracellular signaling cascades, leading to cellular immortalization ( 55 ). Examples of signaling cascades that EBV latent phase proteins engage in in latently infected and transformed cells are shown in Figure 1 , including pro-survival and anti-apoptotic functions of ENBA-1 ( 56 62 ), LMP-1/-2 ( 63 71 ), and EBNA-2,-3,-LP ( 72 74 ) are shown in Figure 1 .…”
Section: Mechanisms Of Ebv Infection and Lymphomagenesismentioning
confidence: 99%
“…Latent viral proteins expression also modulate intracellular signaling cascades, leading to cellular immortalization ( 55 ). Examples of signaling cascades that EBV latent phase proteins engage in in latently infected and transformed cells are shown in Figure 1 , including pro-survival and anti-apoptotic functions of ENBA-1 ( 56 62 ), LMP-1/-2 ( 63 71 ), and EBNA-2,-3,-LP ( 72 74 ) are shown in Figure 1 .…”
Section: Mechanisms Of Ebv Infection and Lymphomagenesismentioning
confidence: 99%
“…J. Wang и соавт. полагают [33], что вирусоносительство связано с повышенной уязвимостью клеток к окислительному стрессу, и доказывают, что ядерный антиген ВЭБ способствует усилению клеточной антиоксидантной защиты. В нашем случае клетки Р3НR-1 в отличие от клеток Namalva характеризуются продукцией антигенов ВЭБ.…”
Section: Discussionunclassified
“…EBV-associated NK/T-cell lymphomas are highly resistant to CHOP, probably due to upregulation of P-gp, an energy-dependent efflux pump that excretes drugs from the cytoplasm to the extracellular space [119,120]. High expression of P-gp is also connected with ROS production, which is induced by EBV infection [121,122]. Previous work established that induction of intracellular ROS production under EBV latent infection elevated P-gp expression via the STAT1 pathway while downregulation of ROS by NecroX-5, an ROS scavenger, effectively attenuated P-gp-associated chemoresistance in EBV-positive NK/T-cell lymphoma [123].…”
Section: Lmp1mentioning
confidence: 99%
“…LMP1 promoted excessive ROS production from EBV-related malignant cells through activation of NAD(P)H oxidases and induction of nuclear factor erythroid 2-related factor 2 (NRF2) [124,125]. Other studies showed that the expression of another EBV-associated protein, EBNA1, in either latent or lytic phases, regulated LMP1 expression [126], and upregulated cellular antioxidant defense to enable B-cell growth, transformation, and immortalization [122].…”
Section: Lmp1mentioning
confidence: 99%